2018
DOI: 10.4236/jilsa.2018.102003
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Rules to Improve Traffic Light Decisions in Urban Roads

Abstract: Many researchers around the world are looking for developing techniques or technologies that cover traditional and recent constraints in urban traffic control. Normally, such traffic devices are facing with a large scale of input data when they must to response in a reliable, suitable and fast way. Because of such statement, the paper is devoted to introduce a proposal for enhancing the traffic light decisions. The principal goal is that a semaphore can provide a correct and fluent vehicular mobility. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Traffic clearance at intersections by giving priority to emergency transit [14][15][16][17][18] extended the green time on detection of emergency vehicle. The recent works in this area include [19] in which a fuzzy inference system uses five input variables to fix the green light interval. Although an 18% improvement in performance was obtained while conducting experiments in simulated environment but due to large scale of inputs the system complexity was high.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traffic clearance at intersections by giving priority to emergency transit [14][15][16][17][18] extended the green time on detection of emergency vehicle. The recent works in this area include [19] in which a fuzzy inference system uses five input variables to fix the green light interval. Although an 18% improvement in performance was obtained while conducting experiments in simulated environment but due to large scale of inputs the system complexity was high.…”
Section: Introductionmentioning
confidence: 99%
“…This made the system less complex and ease of physical implementation. The cost and complexity of the systems [12][13][14][15][16][17][18][19] due to large scale of inputs required was taken care in the proposed design as the system requires inputs in terms of the traffic volume sensed at each lane and detection of EMV. The proposed system in this paper is designed in a way to achieve simplicity in collection of inputs and easy implementation for both busy and underutilized intersection.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that fuzzy controllers effectively reduce the delay. Rocha et al [17] customized a fuzzy inference system that could determine when the semaphore should set the green light interval in accordance with particular road needs. Zuraime et al [18] determined the most efficient and ideal timing for traffic signals to accommodate various traffic densities.…”
Section: Introductionmentioning
confidence: 99%
“…The second module www.ijacsa.thesai.org calculated the green time extension of the chosen phase with the help of queue length as input. Another work [11] considered the possibility to change the green light duration at an isolated four-lane intersection using fuzzy inference system by taking the road condition, traffic and time of the day as major deciding inputs. Researchers in [12] applied fuzzy logic to improve traffic light by taking queue length, arrival flow and exit flow as inputs and calculated the urgency degree using fuzzy rules.…”
Section: Introductionmentioning
confidence: 99%